Coaching special Olympics: A scoping review - Turgeon, S.; Turgeon, J.; Morin, D. (International Journal of Sports Science & Coaching, 2023)
Background Special Olympics enables individuals with an intellectual disability across all continents to take part in sport year-round. Through its mission, Special Olympics provides a setting for athletes that aims to foster performance, participation, and personal development. Coaches play a central role in achieving these outcomes. As such, this scoping review aims to answer the following question: What is known about Special Olympics` coach training and practices?